2016
DOI: 10.32598/ijt.10.2.328.1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effect of Organophosphorus Insecticide Diazinon on Rat Ovary and Protective Effect of Vitamin E

Abstract: Background: Diazinon (DZN) is an organophosphate insecticide widely utilized in agriculture all over the world and causes many negative effects on plants and animal species, especially on human. The aim of present study was to evaluate the effects of DZN on apoptosis of ovarian follicles in adult rats and to assess the protective role of vit E. Methods: Thirty adult female Wistar rats were divided into five groups: control group (without any intervention), sham group (received only pure olive oil, as solvent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Exposure to chlorfenvinphos, another OP has also been linked to generation of ROS and lipid peroxides in rat liver 41 . Moreover, OP like Diazinon induces apoptosis of secondary and graffian follicles in rat ovary 42 . Sivaperumal and Sankar 43 documented that exposure to methyl parathion enhances activities of endogenous antioxidants (including Catalase, Glutathione-s-Transferase, SOD, and MDA) by several folds in fish model.…”
Section: Effects Of Ops On Animal Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…Exposure to chlorfenvinphos, another OP has also been linked to generation of ROS and lipid peroxides in rat liver 41 . Moreover, OP like Diazinon induces apoptosis of secondary and graffian follicles in rat ovary 42 . Sivaperumal and Sankar 43 documented that exposure to methyl parathion enhances activities of endogenous antioxidants (including Catalase, Glutathione-s-Transferase, SOD, and MDA) by several folds in fish model.…”
Section: Effects Of Ops On Animal Modelsmentioning
confidence: 93%
“…Probably the antioxidant property along with acetyl cholinesterase restoration ability plays significant role behind the protective/prophylactic/ameliorative potential of vitamin E. This can be further validated through the fact that supplementation with vitamin E successfully ameliorated CPF-induced haematological and biochemical alterations 74,75 . Vitamin E has been demonstrated to reduce Diazinon induced apoptosis in secondary and graafian follicles in rat ovary 42 . John et al 76 demonstrated that vitamin E has the potential to ameliorate dimethoate and malathion-induced OS in rat erythrocytes.…”
Section: Protective Potential Of Vitamin E Against Op Induced Toxicit...mentioning
confidence: 99%